2015
DOI: 10.1038/ncomms9642
|View full text |Cite
|
Sign up to set email alerts
|

MHC variation sculpts individualized microbial communities that control susceptibility to enteric infection

Abstract: The presentation of protein antigens on the cell surface by major histocompatibility complex (MHC) molecules coordinates vertebrate adaptive immune responses, thereby mediating susceptibility to a variety of autoimmune and infectious diseases. The composition of symbiotic microbial communities (the microbiota) is influenced by host immunity and can have a profound impact on host physiology. Here we use an MHC congenic mouse model to test the hypothesis that genetic variation at MHC genes among individuals medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 55 publications
(86 reference statements)
9
147
1
Order By: Relevance
“…Eα16/NOD and NOD littermates did not differ in the flow cytometric frequency or mean fluorescence intensity of IgA-coated cecal bacteria (Fig. S3), contrary to previous data demonstrating fluctuations in the proportion of IgA + stool bacteria depending on the host MHC allele (19). In our IgA-sequencing data, direct comparisons between the genotypes revealed no OTUs that had significantly different IgA-coating index (ICI) values for either age group (Fig.…”
Section: Comparing the Iga-bound Repertoire Of Cecal Bacteria In Nod Andcontrasting
confidence: 94%
See 2 more Smart Citations
“…Eα16/NOD and NOD littermates did not differ in the flow cytometric frequency or mean fluorescence intensity of IgA-coated cecal bacteria (Fig. S3), contrary to previous data demonstrating fluctuations in the proportion of IgA + stool bacteria depending on the host MHC allele (19). In our IgA-sequencing data, direct comparisons between the genotypes revealed no OTUs that had significantly different IgA-coating index (ICI) values for either age group (Fig.…”
Section: Comparing the Iga-bound Repertoire Of Cecal Bacteria In Nod Andcontrasting
confidence: 94%
“…One possibility is that an additional restriction element, the E complex, could allow immune responses against additional microbial antigens, thereby shaping the developing microbiota. In particular, there could be an effect on the nascent IgA repertoire via presentation of additional microbial antigens, and IgAs are known, in turn, to shape the intestinal microbiota (19,30). We tested the hypothesis that the type of MHC class II allele present would influence the affinity and specificity of the IgA produced in response to the intestinal microbiota of young Eα16/NOD vs. NOD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An experiment in threespined sticklebacks has demonstrated that fish with higher MHC diversity have lower diversity in their gut flora, and that different MHC allele repertoires are associated with shifts in the relative abundance of some bacterial functional groups (Bolnick et al 2014). Recently, Kubinak et al (2015) found that the role of MHC in regulating gut microbial community composition is also applicable to mice, in which specific MHC genotypes reduce the fitness of resident microbiota, favouring systemic infection.…”
Section: Immunity Controls Community Composition and Dynamicsmentioning
confidence: 99%
“…Interestingly, another recent study examined the impact of MHC polymorphisms on the host-commensal bacteria homeostasis and host susceptibility to infection. Here, it was shown that unique host MHC genotypes underlie unique populations of commensal bacteria, with a range of susceptibility to enteric infections among the different commensal populations (103). Although a role for ILC3s was not examined in this context, the primary role of ILC3 MHCII in modulating intestinal homeostasis would suggests that ILC3s may play a causative role in this context.…”
Section: Distinct Antigen-dependent and Antigen-independent Host Pathmentioning
confidence: 99%